Experience of using the technologies of simulation training and simulation business game in the study of the discipline of infectious diseases in children - L. V. Kramar; O. A. Karpukhina; T. Yu. Larina (Детские инфекции (Москва))
The article considers the use of innovative methods of teaching in the form of a business game when studying the discipline «Infectious diseases in children» at the Children’s Infection Diseases Department of the Volgograd State Medical University, which contributes to the formation of professional skills based on knowledge and the development of creative abilities. There are presented methodology for organizing and conducting a business game is presented on the example of a simulation mannequin of a child of the first months of life with clinical symptoms of measles.